How Do Work Motivation, Rewards, and Punishments Impact Employee Performance? An Approach in Islamic Economics - Sumadi, Sumadi; Santoso, Ivan Rahmat (Universitas Islam Negeri Raden Intan Lampung, 2022)
Employee performance is a crucial element in supporting success in a company, but studies so far have prioritized research in conventional contexts. This study aims to determine the effect of the application of work motivation, reward, and punishment on employee performance based on an Islamic economic perspective. The quantitative approach used in this study was tested on a sample of 30 employees at CV General Solo. The data analysis technique uses Multiple Linear Regression Analysis with the help of the SPSS tool. The results of the study found that only work motivation had a significant effect on employee performance with a sig value of 0,045. In addition, simultaneously work motivation, reward and punishment affect employee performance with a value of 31,1%. Employee motivation that is in line with the goals of Islamic economics has an impact on improving employee performance. Giving rewards and punishments proportionally to employee performance can lead to the application of the Islamic economic system for better performance even though the findings are found at a small significant level. The research implications have an impact on improving employee performance following Islamic values.